(untitled) (Research, Society and Development, 2025)
Nursing plays an essential role in elderly care, promoting physical and mental well-being, yet faces daily challenges in its care. The objective is to understand the challenges nursing faces in elderly care. This is a descriptive field study with a literature review addressing nursing challenges in elderly care. The study was conducted through interviews and questionnaires at an association located in Manaus, Amazonas, Brazil. The data collected reveal the care provided and the procedures adopted. The results highlight the importance of nursing in identifying challenges in the healthcare process, such as limited access and lack of information, and emphasize the need for measures to promote health and well-being. The conclusion is that nursing faces obstacles when providing care to elderly individuals in various home settings.